Paremiological units of praise expression in English culture - Kadirova Dilfuza Alisherovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article deals with paremiological units of praise expressions in English culture. The ability of language to express human appreance through paremiological units is examined.